Epidemiological profile of oral and maxillofacial trauma in a reference hospital in the interior of Bahia (Research, Society and Development, 2022)
Objective: To analyze the epidemiological profile of patients with oral and maxillofacial trauma treated at the Hospital Geral Prado Valadares in Jequié, Bahia. Methodology: This is a descriptive research of quantitative approach, through a documentary research, through the medical records of patients involved in oral and maxillofacial trauma in HGPV in Jequié - BA in the period from June 2018 to June 2021.  Relative and absolute frequency were used to describe the variables. Multinominal logistic regression was also performed to calculate the OddsRatio. The significance level adopted for the hypothesis tests was p-value 0.05. The data were tabulated in Microsoft Excel and subsequently analyzed in IBM Statistical Package For Social Science (version 21.0). Results: Male gender was more prevalent 80.6% (733), and the most prevalent age group for this group was between 19 to 30 years old with 29.6% (217) and the lowest for individuals over 61 years old with 8.6% (63) only. Regarding etiology, the motorcycle accident was more prevalent overall with 35.4% (322). Nonalcohol consumption was more prevalent in both genders, as was treatment. However, the most affected sites differed where for males fractures of the middle 1/3 of the face were more prevalent 41.2% (302). Conclusion: Male individuals aged between 19 and 60 years had a higher prevalence of traffic accidents resulting in maxillofacial injuries, with alcohol consumption resulting in fractures of the middle 1/3 of the face, with a higher concentration on weekends.